2020
DOI: 10.1136/vetreccr-2019-001063
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive buprenorphine associated intraoperative apnoea and prolonged recovery in a giant panda (Ailuropoda melanoleuca) during castration for testicular neoplasia

Abstract: A 14-year-old giant panda presented with unilateral scrotal swelling. Palpation and conscious ultrasound were suggestive of testicular neoplasia. Anaesthesia was required to obtain radiographs and MRI. Immobilisation was achieved with ketamine and medetomidine, and anaesthesia was maintained with sevoflurane in oxygen. Tumours were discovered in both testes and castration was performed. before surgery buprenorphine was administered by slow intravenous injection. Apnoea occurred after approximately 10 mcg/kg ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…A comparably low dose of medetomidine has been previously described (0.035–0.04 mg/kg) in a similar drug protocol in giant pandas. 6,8,12 The ketamine dose used in this study was lower than in previously reported ketamine-only protocols, but in this study they were used in combination with medetomidine. 7…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…A comparably low dose of medetomidine has been previously described (0.035–0.04 mg/kg) in a similar drug protocol in giant pandas. 6,8,12 The ketamine dose used in this study was lower than in previously reported ketamine-only protocols, but in this study they were used in combination with medetomidine. 7…”
Section: Discussionmentioning
confidence: 93%
“…A comparably low dose of medetomidine has been previously described (0.035-0.04 mg/kg) in a similar drug protocol in giant pandas. 6,8,12 The ketamine dose used in this study was lower than in previously reported ketamine-only protocols, but in this study they were used in combination with medetomidine. 7 The first signs of sedation (slowing down, ataxia, and dropping the head) appeared quickly, and the pandas went into sternal recumbency without reaction to external stimuli in less than 5 min, which was much faster than previously reported in giant pandas with ketamine alone (16.4 6 12 min and 12.2 6 15.7 min), ketamine-diazepam (22.7 6 8.7 min), ketamine-xylazine (8.8 6 6.6 min and 18 6 26 min), tiletamine-zolazepam (10.7 6 5.5 min), tiletamine-zolazepam-ketamine (7.0 6 4.3 min) tiletamine-zolazepam-ketamine-medetomidine (6.23 6 6.34 min), and dexmedetomidine-tiletamine-zolazepam (8[7-12] min).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations